United we stand - Birmingham, John, 1964-; Nye, Jody Lynn, 1957-; Trent, Brian; Hoyt, Sarah A.; Ibson, Jamie; Freer, Dave; Barber, Griffin; Sherrer, Lydia; Todd, Mel; Smith, Christopher L. (Christopher Lee), 1975-; Massa, Mike, 1967- (Ringo, John, 1963- Black tide rising, 2024)
"The world was brought to its knees by the zombie virus. But humanity has risen from the ashes and has begun to rebuild. Courageous men and women have kindled a fire of hope in the darkness. But mere survival is not enough. The real challenge is how to keep that future alive. How to not just survive, not just to rebuild, but actually thrive. To tell the universe that mankind can take whatever nature throws against us and not back down. To stand united. Stories by John Birmingham, Jody Lynn Nye, Jamie Ibson, Sarah A. Hoyt, Brian Trent, Dave Freer, Griffin Barber, Lydia Sherrer, Mel Todd, Christopher L. Smith, and Mike Massa"--